Main Peran Dalam Konsumsi Barang Mewah Imitasi Oleh Perempuan Kalangan Atas - Larasati P. A., Made; N. Firman, Vadya; Ardianto, Eka; Ali, Alavi (Kajian Branding Indonesia, 2024)
Since the luxury goods industry is developing, the same thing goes to the counterfeit luxury goods industry. Surprisingly, based on the evidence gathered there is a big potential for the upper class who can afford the real goods to buy the counterfeit ones. This study aims to understand the consuming process and the reasons why those upper class people buy and use it. This study is a descriptive qualitative study with phenomenology (IPA) approach by interviewing the informants who meet the criteria. Results show that all informants came from different ages and they are all categorized into the upper class classification. All the data gathered and classified into three superordinates based on the way how they portray themselves in their environment; “vulnerable buyer” (easily influenced, intimidating brands, & confusing preferences), “passionate scammer” (high confidence, manipulative personality, & validation seeker), & “adaptive socialite” (demanding critiques, different settings, & social media anxiety).